English Translation of Political Documents with Chinese Characteristics from the Perspective of Eco-Translatology: – A Case Study of the Report on the Work of the Government (2023) - Liu, Yunqi; Wei, Lexin; Li, Jiajia (Transactions on Social Science, Education and Humanities Research, 2024)
In today’s increasingly globalized world, foreign publicity is particularly important in the exchanges and cooperation between nations, among which the translation of political documents serves as a crucial channel. The Report on the Work of the Government summarizes China’s work over the past year and outlines the prospects for the coming year. Its English translation is often highly concerned both domestically and internationally, making it an important text for foreign publicity. Based on the theory of Eco-translatology, this study takes the English version of the Report on the Work of the Government (2023) as an example to explore how to highlight cultural confidence and achieve communicative purposes in the translation of foreign publicity represented by political documents. It is found that translators often employ translation strategies, such as free translation, addition, omission, combination and annotation to realize the adaptive selection of translation in linguistic, culture and communication, facilitating full interaction between the source and target cultures, thereby enhancing the international influence and dissemination power of Chinese discourse.